Is professional regulation a highway to social immobility at top? Social closure and gendered outcomes in Italy - Ruggera Lucia; Erola Jani (Turun yliopisto, 2025)
This article examines how processes of social closure promote persistence at the top of the occupational hierarchy and how it varies by gender. We focus on the link between professional closure strategies and intergenerational immobility in professional employment in Italy. Since Italian professions display the highest levels of service market regulation across Europe and are the largest occupational group within the upper class, analyzing the link between professional closure and social inequality is crucial. ISTAT´s survey on Italian graduates (SPL, 2011), the Origin-Destination association is investigated at big-, meso- and micro-level with log-linear nested models. This sample offers in analyzing social mobility at the beginning of professionals’ careers and provide in-depth explanations of micro-level dynamics of social reproduction. The analyses indicate that children of regulated professionals have a higher propensity to follow in their parents’ footsteps (micro-classes). Self-employment functions as an independent dimension, which strongly increases intergenerational immobility at top similarly for professionals and larger entrepreneurs (meso- and micro-classes). Finally, it demonstrates that the combination of specific parental resources strongly facilitates professionals’ children to avoid social demotion (big-classes).